Investigation of correlations between DNA methylation, suicidal behavior and aging. (9th March 2017) - Jeremian, Richie; Chen, Yi‐an; De Luca, Vincenzo; Vincent, John B; Kennedy, James L; Zai, Clement C; Strauss, John
Abstract : Objectives: Suicidal behavior (SB) is a major cause of mortality for patients diagnosed with bipolar disorder (BD). In this study, we investigated epigenetic differences in BD participants with and without a history of SB. Methods: We used suicidality scores constructed from Schedule for Clinical Assessments in Neuropsychiatry (SCAN) interview questions about suicidal thought and behavior to identify individuals from a BD cohort of n=452; participants with the most extreme high (H‐SB, n=18) and most extreme low (L‐SB, n=22) scores were used as cases and controls, respectively. Epigenome‐wide DNA methylation patterns were compared between the two groups using the Illumina Infinium Human Methylation 450 BeadChip microarray. DNA methylation age was compared to chronological tissue age. Results: We observed highly significant differences in methylation between cases and controls in three genomic regions enriched for epigenetic modifications corresponding to gene regulatory regions. BD participants with a history of SB showed less overall methylation in the 5′ untranslated region of Membrane palmitoylated protein 4 ( MPP4 ) ( P =7.42×10 −7 ) and in intron 3 of TRE2/BUB2/CDC16 domain family member 16 ( TBC1D16 ) ( P =6.47×10 −7 ), while exon 1 of Nucleoporin 133 ( NUP133 ) was less methylated in controls ( P =1.17x10 ‐6 ). Moreover, we observed a greater correlation between DNA methylation age and tissue age in controls ( r =.91, P <.0001) than in the H‐SB group ( r =.83, P <.0001). Conclusions: We report significant findings at three loci based on a methylome scan of participants with BD for an SB phenotype, and potentially altered molecular aging in suicide attempters. Despite the small sample size, our proof‐of‐concept study highlights the potential for epigenetic factors to be useful in understanding the molecular underpinnings of suicide with the ultimate aim of its prevention.